Pemberdayaan Ibu-ibu PKK melalui Inovasi Produk Kosmetik Alami Berbasis TOGA di Perumahan Green Semesta Semarang - Dyah Palupiningtyas; Krisnawati Setyaningrum Nugraheni; Ambar Dwi Erawati; Yema Charista Zelda; Ani Puspitasari (Jurnal Pengabdian Masyarakat Waradin, 2025)
This community service program aimed to empower women from the Family Welfare Program (PKK) in Green Semesta Housing, Semarang through the innovation of natural cosmetic products based on medicinal plants (TOGA). The "housewife creative" approach was used to optimize the participants' creative potential. Activities included training on natural cosmetic production, entrepreneurship workshops, and intensive mentoring. As a result, two innovative products were created: "Lulur Herbal Semesta" and "Green Glow Body Scrub". Participants' knowledge and skills increased by 75%. A business group called "Semesta Herbal Beauty" was formed, showing the program's sustainability potential. The use of simple technology and innovation based on local wisdom proved effective in increasing productivity and product quality. This program demonstrates the potential for community economic empowerment through optimizing local resources.